2023
DOI: 10.1038/s41598-023-33717-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term uptake rate of a breast cancer screening program in Fukushima, Japan, following the 2011 Triple Disaster: a retrospective observational study

Abstract: Little is known about how crises might affect the long-term uptake of breast cancer screening programs. This study aimed to clarify the long-term trend of breast cancer screening program uptake in Minamisoma City following the 2011 Triple Disaster in Fukushima, Japan (earthquake, tsunami, and nuclear disaster), and to evaluate the factors associated with this uptake. This study retrospectively analyzed data from the Basic Resident Registry and Breast Cancer Screening Program in Minamisoma City following the Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
4
0
0
Order By: Relevance
“…The current observation aligns with findings from our previous research on the long-term trends of breast cancer screening rates in areas affected by the Great East Japan Earthquake [46]. In the study, one of the factors identified for not undergoing breast cancer screening post-disaster was the absence of a screening history before the earthquake [46]. Given these consistent findings across different crises, it becomes imperative to establish early and regular screening habits in individuals, as such habits prove resilient even in the face of significant adversities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current observation aligns with findings from our previous research on the long-term trends of breast cancer screening rates in areas affected by the Great East Japan Earthquake [46]. In the study, one of the factors identified for not undergoing breast cancer screening post-disaster was the absence of a screening history before the earthquake [46]. Given these consistent findings across different crises, it becomes imperative to establish early and regular screening habits in individuals, as such habits prove resilient even in the face of significant adversities.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the participants who had regularly undergone screenings before COVID-19 demonstrated an 85.3% post-pandemic uptake rate. The current observation aligns with findings from our previous research on the long-term trends of breast cancer screening rates in areas affected by the Great East Japan Earthquake [46]. In the study, one of the factors identified for not undergoing breast cancer screening post-disaster was the absence of a screening history before the earthquake [46].…”
Section: Discussionsupporting
confidence: 90%
“…The current observation aligns with ndings from our previous research on the long-term trends of breast cancer screening rates in areas affected by the Great East Japan Earthquake [44]. In the study, one of the factors identi ed for not undergoing breast cancer screening post-disaster was the absence of a screening history before the earthquake [44]. Given these consistent ndings across different crises, it becomes imperative to establish early and regular screening habits in individuals, as such habits prove resilient even in the face of signi cant adversities.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the participants who had regularly undergone screenings before COVID-19 demonstrated an 85.3% uptake rate post-pandemic. The current observation aligns with ndings from our previous research on the long-term trends of breast cancer screening rates in areas affected by the Great East Japan Earthquake [44]. In the study, one of the factors identi ed for not undergoing breast cancer screening post-disaster was the absence of a screening history before the earthquake [44].…”
Section: Discussionsupporting
confidence: 89%